Closing Ceremony International Conference On Bioengineering and Technology (IConBET) & MOU UMK and SPMVV - Universiti Malaysia Kelantan, Perpustakaan (2023)
Closing Ceremony International Conference On Bioengineering and Technology Dan MOU UMK and SPMVV(IConBET) yang telah diadakan di Hotel Grand Riverview, Kota Bharu